HUBUNGAN MINAT BELAJAR DENGAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI GUGUS III KECAMATAN RUMBAI KOTA PEKANBARU - Siska Wulandari; Hendri Marhadi; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research was motivated by the low results obtained by the social studies students. Researchers speculate that one contributing factor is the lack of interest of the students towards social studies, and the assumption that social studies is a boring subject. The aim of this research was to determine the relationship of class IV student interest Cluster III Elementary School District of Rumbai, Pekanbaru learning outcomes social science. This research is expected to provide benefits as a description of the relationship between interest in learning outcomes and how much influence exerted by these interests. In this study, the research is a Cluster III State Elementary School District of Rumbai, Pekanbaru in class IV. As in this study, researchers used a descriptive quantitative study aimed to describe and create a picture of the relationship between interest in learning with student learning outcomes. In the implementation of this research instrument used is the questionnaire technique. The study population numbered 340 students, of the total population of the research samples taken as many as 102 students. Results from these studies it is known that there is a relationship between interest in learning with learning outcomes in which the correlation coefficient of 0.241. 0,241  0. Ha accepted, which means there is a significant relationship between the variables x (interest in learning) with variable y (learning) with a low degree of relationship between variables. For significance, showing that the obtained thitung ttable 2.479 and 1.984. If thitung ≥ ttable, 2.479 ≥ 1.984 then Ho is rejected. This means that there is a significant relationship between interest in learning with student learning outcomes. Interest in learning gives the relationship of 5.8% and 94.2% by other factors beyond the variables used. Therefore the authors submit suggestions, which are expected in implementing teacher learning is able to generate interest in learning the lesson it with a variety of ways, both the methods used, techniques vary, and others.Key Words: interest learn, result of learning